Critical reading and writing for postgraduates - Wallace, Mike; Wray, Alison (Sage study skills, 2006)
Focusing on critical reading and self-critical writing, this book is suitable for postgraduate students and early-career academics. It contains tools for analysing texts and structuring critical reviews, and incorporates exercises and worked examples drawn from the social sciences